Penal cultures and female desistance - Österman, Linnéa Anna Margareta (International series on desistance and rehabilitation, 2018)
Introducing penal cultures and female desistance -- Gender, penality and desistance in cross-national contexts -- Researching women's journey towards desistance in diverse cultures and contexts -- Mapping the female offender's journey : points of departure -- Penological landscapes and female perspectives : "Nordic exceptionalism" and "Anglophone excess" -- The female route out : barriers, "ladders" and the role of relationality -- The female route out : employment, inclusion and participation -- Concluding thoughts on penal cultures and female desistance -- Bibliography -- Appendix: Pen portraits